Process of Producing High-Octane Motor Fuel Components from Straight-Run Gasolines on Modified Zeolite Catalysts; Chemistry and Technology of Fuels and Oils; Vol. 53, iss. 4 - Khomyakov I. S. Ivan Sergeevich (2017, 2017)
Title screen